Greening Polish transportation? Untangling the nexus between electric mobility and a carbon-based regime. (January 2022) - Lis, Aleksandra; Szymanowski, Rafał
Highlights: We combine the multi-level perspective (MLP) and historical institutionalism (HI). Electric mobility transition becomes embedded in the incumbent energy regime. While Polish state-led EM projects have failed, niche ventures expand on international markets. Successful projects do not green Polish transport but support sustainable transitions elsewhere. Ultimately, the role of the state is crucial in steering electric mobility transition. Abstract: This paper examines electric mobility transition in Poland which dates back to the beginning of the 1990s when Polish niche-level actors started to innovate with new technologies for low carbon transportation. By drawing on the multi-level perspective (MLP) on sustainability transitions in combination with historical institutionalism (HI) in political economy, the analysis reconstructs patterns of interactions between regime- and niche-level actors running projects in e-mobility. We pursue a two-pronged, mixed-method empirical approach that uses primary written sources and semi-structured expert interviews (N = 25) with key actors in the field. Such an approach allows us to study e-mobility transition as embedded in the incumbent energy regime of a given country. The case of Poland reveals heavy reliance on coal for electricity production and difficulties to break away from the fossil fuel regime, both in the energy and transportation sector. We find that the e-mobility transition in Poland is a double-paced process, where projects led by Polish state actors have failed thus far, while projects led by private, niche-level actors met with international interest. At the same time, the analysis shows that the successful ventures may not necessarily green Poland's transportation system, but their performance at international markets may rather contribute to e-mobility transitions in other parts of the world.